A novel opioid/pramipexole combination treatment for the management of acute pain: a pilot study - Girardi, Cara; Duronio, Joseph; Patton, Ryan; O’Brien, Kevin; Clemens, Stefan; Brewer, Kori L. (Frontiers in Pain Research, 2024)
PurposeDespite their dangerous side effects, opioid drugs remain a standard of care for moderate to severe pain with few alternatives. Strategies to maintain the analgesic effects of opioids while minimizing the associated risks are needed. Pre-clinical studies have shown using a dopamine 3 receptor (D3R) agonist as an adjuvant to morphine provides superior analgesia against painful stimuli compared to morphine alone. Our objective was to test if adjunct treatment with a D3R agonist can lead to a reduction in opioid use while maintaining effective analgesia.Patients and methodsThis study was set up as a double-blinded, placebo-controlled randomized trial. Enrollment included acute renal colic patients presenting to the emergency department, from which patients were randomized to either the “control” or “study arm”. The control group received standard treatment of care (morphine, 0.1 mg/kg; i.v.) and an oral placebo pill. The experimental group received half-dosed morphine and oral pramipexole pill (0.25 mg). Pain measurements including a numerical pain scale and visual analog scale were collected from enrollees at baseline and every subsequent 15 min.ResultsA total of 19 patients completed the study, 10 in the experimental arm and 9 in the control arm. During the study period, effective analgesia (50% decrease from baseline) was achieved in 80% of patients in the experimental arm vs. 33.3% in the control arm.ConclusionOur pilot clinical trial demonstrated that D3R recruitment can serve as an effective adjuvant to low-dose morphine for control of renal colic pain and potentially other acute pain conditions. Clinical Trial RegistrationClinicalTrials.gov, identifier, (NCT04160520).